Firm training and wage rigidity - Wolfgang Lechthaler (Kiel Institute for the World Economy (IfW), 2008)
Although wage rigidity is among the most prominent subjects in modern economics, its effects on wage compression and firm training have thus far not been considered. This paper is trying to bridge this gap by using a simple two period model which can still by analyzed analytically. I am able to show that wage rigidity increases wage compression. However, contrary to previous work this is not sufficient to increase firms' training investments. The reason lies in the endogeneity of separations, which become more frequent.
Keywords: J24; J31; M53; 330; Human capital; wage rigidity; training; Betriebliche Bildungsarbeit; Lohnstruktur; Betriebliche Bildungsarbeit; Bildungsinvestition; Theorie